Double Deletion of EP402R and EP153R in the Attenuated Lv17/WB/Rie1 African Swine Fever Virus (ASFV) Enhances Safety, Provides DIVA Compatibility, and Confers Complete Protection Against a Genotype II Virulent Strain - Carmina Gallardo; István Mészáros; Alejandro Soler; Jovita Fernandez-Pinero; Erwin van den Born; Alicia Simón; Nadia Casado; Raquel Nieto; Covadonga Perez; Irene Aldea; Vicente Lopez-Chavarrias; Eszter Göltl; et al. (Vaccines)
Background/Objectives: African swine fever virus (ASFV) is a devastating disease affecting domestic and wild suids and causing significant economic losses in the global pig industry. Attenuated modified live virus (MLV) vaccines are the most promising approaches for vaccine development. This study aimed to evaluate the safety and efficacy of four recombinant ASFV genotype II strains, derived from the non-hemadsorbing (non-HAD) attenuated isolate Lv17/WB/Rie1, through the single or simultaneous deletion of virulence-associated genes. Methods: Recombinant viruses were engineered by deleting the UK, EP402R, and EP153R genes, either individually or in combination. Four recombinant strains were evaluated for safety and efficacy in domestic pigs vaccinated intramuscularly with 102 TCID₅₀. Clinical signs, viremia, virus shedding, and antibody responses were monitored. Protection efficacy was assessed by challenging vaccinated pigs with the virulent genotype II Armenia07 strain. Additionally, a reversion-to-virulence study involving an overdose of the vaccine candidate was conducted to evaluate its stability through serial immunizations. Results: Deletion of the UK gene alone increased virulence, whereas the double deletion of EP402R and EP153R (Lv17/WB/Rie1-ΔCD) significantly enhanced safety while maintaining full protective efficacy. Vaccinated pigs exhibited reduced viremia, no virus shedding, and robust virus-specific antibody responses, achieving complete protection against Armenia07. The reversion-to-virulence study revealed potential but limited pathogenicity after multiple passages, indicating areas for improvement in vaccine stability. Conclusions: The Lv17/WB/Rie1-ΔCD strain demonstrates excellent safety and efficacy, along with potential DIVA (differentiating infected from vaccinated animals) compatibility, positioning it as a strong candidate for an ASFV MLV vaccine. Further research is needed to refine the vaccine and address the potential risks of reversion to virulence.